2016
DOI: 10.4137/jcnsd.s38359
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Assessment of Obsessive–Compulsive Disorder

Abstract: Obsessive–compulsive disorder (OCD) is a neuropsychiatric illness that often develops in childhood, affects 1%–2% of the population, and causes significant impairment across the lifespan. The first step in identifying and treating OCD is a thorough evidence-based assessment. This paper reviews the administration pragmatics, psychometric properties, and limitations of commonly used assessment measures for adults and youths with OCD. This includes diagnostic interviews, clinician-administered symptom severity sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 153 publications
1
49
0
2
Order By: Relevance
“…The international standard for the assessment of symptom severity and outcome in treatment trials of pediatric obsessive-compulsive disorder (OCD) is the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS [1,2]). The CY-BOCS is a clinician-administered interview that includes a symptom checklist followed by severity ratings for obsessions and compulsions, yielding an overall severity score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The international standard for the assessment of symptom severity and outcome in treatment trials of pediatric obsessive-compulsive disorder (OCD) is the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS [1,2]). The CY-BOCS is a clinician-administered interview that includes a symptom checklist followed by severity ratings for obsessions and compulsions, yielding an overall severity score.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, self-report scales with sustained precision and validity have the potential to save time and resources for clinicians, which in turn can make assessments of OCD more scalable and facilitate costeffective ways of evaluating interventions. According to a review by Rapp et al [2], there are several self-reported measures for pediatric OCD: the CY-BOCS-Child Report [4]; the Obsessive Compulsive Inventory -Child Version (OCI-CV [5]); the Children's Florida Obsessive Compulsive Inventory (C-FOCI [6]); and the Children's Obsessional Compulsive Inventory (ChOCI [7]). Although all of these are promising measures to assess OCD symptoms, the OCI-CV [5] is the only self-report measure that captures the multidimensionality of OCD in youth.…”
Section: Introductionmentioning
confidence: 99%
“…The main outcome measure was the change in psychometric scales score associated with symptomatic manifestation. Results are presented for the Y-BOCS (n = 7) or Padua Inventory-Washington State University Revision (PI-WSUR; n = 1 (Rapp et al, 2016)) since both scales evaluate the severity of obsessive-compulsive symptoms ( Table 2). Psychometric scales assessing other parameters (e.g.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…OCD is the fourth most common psychiatric disorder and the tenth cause of disability worldwide. OCD is characterized by recurrent thoughts (obsessions) associated with high anxiety, followed by repetitive behaviors or mental tasks to relieve the anxiety (compulsions) (Rapp et al, 2016;Sachs and Erfurth, 2018). Anxiety symptoms comprise autonomic nervous system dysregulation namely increased heart rate, decreased heart rate variability, elevated skin electrodermal activity, and augmented breathing rate (Schoenberg and David, 2014;Simon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, lifetime prevalence estimates for OCD are approximately 2%. [1] Two popular and well-characterized treatments for OCD are cognitive behavior therapy and selective serotonin reuptake inhibitors, with 40% to 60% of patients achieving significant symptomatic improvement. [2] However, approximately 10% of patients exhibit no improvement despite long-term treatment with various therapies and are considered to have severe, treatment refractory OCD.…”
Section: Introductionmentioning
confidence: 99%